Enhancing Arabic Proficiency through Content and Language Integrated Learning: Implementation and Challenges in Pesantren - Muhammad Iqbal; Mohammad Ahsanuddin; Muhammad Alfan (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
The Arabic language plays a crucial role in Islamic education, particularly in understanding Islamic sciences. However, traditional teaching methods often lack innovation, resulting in challenges such as limited vocabulary acquisition and insufficient speaking practice. This study examines the implementation of the Content and Language Integrated Learning (CLIL) method in Arabic language instruction at Pesantren Tahfizh Al-Bassam. Using a qualitative approach with a case study method, this research explores CLIL implementation strategies, challenges encountered, and its impact on students. The findings indicate that CLIL enhances Arabic language skills, both oral and written, while also accelerating vocabulary acquisition and improving comprehension of Islamic studies. Pesantren strategies include teacher training, CLIL integration into the curriculum, and project-based assessments such as Arabic-language drama performances and short video production. While CLIL proves effective, challenges remain, including a shortage of qualified teaching staff and a lack of instructional materials. To address these issues, Pesantren organizes intensive teacher training and incorporates artificial intelligence (AI)-based technology into learning. This study concludes that CLIL is an innovative and effective approach to improving Arabic language education in Pesantren. With adequate support, this method has the potential to become a standardized approach to Arabic instruction in Islamic educational institutions.